Autophagy-Based Unconventional Secretory for AIM2 Inflammasome Drives DNA Damage Resistance During Intervertebral Disc Degeneration - Li, Shuai; Liao, Zhiwei; Luo, Rongjin; Song, Yu; Wang, Kun; Feng, Xiaobo; Ou, Yangliu; Wu, Xinghuo; Zhang, Yukun; Gao, Yong; Yin, Huipeng; Yang, Cao (Frontiers in Cell and Developmental Biology, 2021)
Intervertebral disc degeneration (IDD) is the primary cause of low back pain. Stress-induced DNA damage is closely relevant to the pathogenesis of IDD; however, the underlying mechanisms remain unclear. This study investigated the role of the absent in melanoma 2 (AIM2) inflammasome as a DNA damage sensor in nucleus pulposus (NP) cells. We found that the level of AIM2 increased in degenerated discs and was correlated to the degree of IDD. Knockdown of AIM2 ameliorated H2O2-induced DNA damage and apoptosis in NP cells in vitro, and retarded the progression of IDD in vivo. Furthermore, the induction of autophagy protected against cellular DNA damage via the unconventional secretion of AIM2. We further identified the Golgi re-assembly and stacking protein 55 (GRASP55) as mediator of the transport and secretion of AIM2 via an autophagic pathway. Taken together, our researches illustrate the role and regulatory mechanism of the AIM2 inflammasome during IDD. Targeting the AIM2 inflammasome may offer a promising therapeutic strategy for patients with IDD.